Parametric Identification of a Model of the Unloading Process of an Universal Trailer - Celmerowski, A.; Masłowski, A. (Engineering Transactions, 1991)
Parametric identification of a certain discrete, one-dimensional, nonlinear mathematical model is presented in the paper; concerning the process of unloading of an universal agricultural trailer. The identification problem is formulated as a problem of numerical minimization and solved by means of the COMPLEX algorithm. The numerical results obtained are illustrated by the example of hard coal unloading from the RT-1/3.5 type trailer.